Implications of the Role of Tourism Carrying Capacity in the Development of Sustainable Tourism Destinations - Haribudiman, Irwan; Berliandaldo, Mahardhika; Holman Fasa, Angga Wijaya (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Tourism contributes to increasing global and national Gross Domestic Product (GDP) growth. However, there are also negative impacts on tourism activities. One of the implementations to minimize negative impacts can be carried out by applying the carrying capacity of the destination (tourism carrying capacity/TCC). This study aims to determine the implications of the role of tourism carrying capacity in sustainable tourism development, which focuses on the causality relationship between tourism destination governance policies and tourism carrying capacity (TCC). This study uses a qualitative library/desk study method with a Driving Forces, Pressures, State, Impacts, and Responses (DPSIR) framework analysis approach. The five dimensions of the carrying capacity of tourism destinations used in the DPSIR framework are territorial, governance, economic, social, and environmental. As a result, three framework findings and strategic analysis implications were obtained. First, it required the restoration of natural resources, environment, and ecosystems; second, carrying out integrated planning in land use, economic growth, strengthening socio-demographics, and a sustainable environment; third, educating tourists to transform the attitude, behavior, and ethics of tourists. The overall strategic analysis framework aligns with various tourism development programs to maintain natural, economic, social, and environmental balances that apply sustainable tourism by implementing stakeholder cooperation.